Criterios de la traducción ideal (Journal of the College of Basic Education, 2023)
That all languages, including Spanish and Arabic characterized its proximity to a large amount of complexity and language difficulties and uses grammatical wrong and mystery that might get in, and applies perfectly this case on the Spanish language, especially when we are translated into Arabic and vice versa, which revolves discussed this on a perfect translation into Arabic language through a good understanding and knowledge of language differences, which require a large and challenging issue in preparation for a broad and ability and proficiency to be reckoned with by the translator. That it should be at least proficiency in two languages and two movable ones and target language, because the translation process is not an easy task or easy as thinking is believed by many, it is quite the contrary, it is the process of a very difficult and complex, it does not consist of the conversion and transfer process a word or phrase or a particular phrase from one language to another only because if we accept this concept will be able to anyone that opens the book dictionary, or to preserve a set of words and become a translator in this case, while the truth is not quite you